SOSIALISASI PEDULI LINGKUNGAN TERHADAP PELESTARIAN KAWASAN WISATA MANGGROVE KUALA LANGSA - Elisa Putri; Zakia Tutdin; Hamidah Hanim (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Kuala Langsa is a mangrove tourist area located in Langsa City, Aceh Province. Currently, the Kuala Langsa Mangrove Forest tour is a tourist spot that is of interest to the public. However, tourists and snack traders are not disciplined towards the behavior of protecting the environment. This community service (PKM) activity aimed to reduce the littering behavior or activities of the community. Partners in this PKM activity were snack traders and mangrove tourists. The implementation of this activity was carried out in three stages, namely: first stage, the team prepared permits from the village head; the second stage, the team prepared material requirements for carrying out activities such as leaflets or brochures, organic and non-organic waste bins, then carried out outreach and education to snack traders and tourists; and the third stage, namely the evaluation stage. The result of implementing this community service activity was the foster of sense of community concern for the preservation of mangrove forest tourism areas, namely by providing socialization and education. Changes in the behavior or activities of the hawker traders, it can be seen that the traders have collected the trade waste and disposed of it in a landfill.